Unnecessity of Routine Dissection of Right Central Lymph Nodes in cN0 Papillary Thyroid Carcinoma Located at the Left Thyroid Lobe - Zhang, Songtao; Zhang, Runfang; Wang, Chao; Gong, Wenbo; Zheng, Chen; Fang, Qigen; Dai, Liyuan (Frontiers in Oncology, 2021)
Objective: The lymph node posterior to the right recurrent laryngeal nerve (LN-prRLN) is an important part of the central lymph nodes (LNs). We aimed to explore the rate and predictors of LN-prRLN metastasis in cN0 papillary thyroid carcinoma (PTC) located at the left thyroid lobe. Methods: Patients with surgically treated primary left lobe PTC were retrospectively enrolled. The metastatic distribution of LN-prRLN and postoperative complications were assessed. The association between LN-prRLN metastasis and clinicopathological variables was evaluated by univariate and multivariate analyses. Results: A total of 857 patients were included for the analysis. Central LN metastasis was noted in 310 (35.3%) cases. The most (27.6%) and least (1.7%) commonly involved LNs were the left paratracheal LN and the LN-prRLN. In the univariate analysis, the tumor size, multifocality, the extent of extrathyroidal extension (none vs. macroscopic vs. macroscopic maximal), and perineural invasion were associated with positive LN-prRLN. In the multivariate analysis, tumor size of >40.0 mm and macroscopic maximal invasion were found as the only two independent predictors. Transient and permanent hypoparathyroidism were noted in 90 (10.2%) and 13 (1.5%) patients, respectively. Voice change was noted in 40 (4.6%) patients, and 20 patients recovered. Conclusions: In cN0 PTC located at the left lobe, LN-prRLN metastasis was very uncommon. We found that LN-prRLN dissection is not required routinely, but should be performed if the tumor size is >40.0 mm and macroscopic maximal extrathyroidal extension is present.